IMPACT OF CLIMATE CHANGE ON MILLET YIELD IN INDIA SINCE 1991: AN ECONOMETRIC ANALYSIS - KRISHNA KUMAR JADAUN* and AKRAM AHMAD KHAN (The Journal of Research ANGRAU, 2023)
This study examines the effects of climate change on millet yield in India using secondarydata for thirty years (1991-2020). The variation in agricultural millet production in India is estimatedusing average annual temperature, precipitation, CO2 emissions per capita, and the ruralpopulation. Assessing the order of integration using the unit root test and augmented DickeyFuller (ADF). Estimations of the unit root demonstrate that all variables are stationary at the leveland first difference. The autoregressive distributive lag (ARDL) bound test is applied to establishthe relationship between variables. The study demonstrates that the average yearly temperaturehas a negative and significant effect on millet yield, whereas, CO2 emission per capita has afavourable long-term impact on millet yield. In India, 1% increase in yearly average temperatureresults in a 3.06% decrease in millet yield, while 1% increase in CO2 emissions per capita resultsin a 0.42% gain in millet yield on average. In the short run, independent variables do not affectmillet yield. As the population of India grows, the nation will face food security issues. There is aneed for strategies to mitigate the negative impact of temperature on agricultural yield and securesufficient food for a growing population